2020
DOI: 10.3389/fphys.2020.00123
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing RNAi Efficiency to Decipher the Functional Response of Potential Genes in Bemisia tabaci AsiaII-1 (Gennadius) Through dsRNA Feeding Assays

Abstract: Whitefly Bemisia tabaci is a global invasive pest that causes substantial losses to agricultural crops worldwide either by direct feeding or vectoring numerous plant viruses. Management with insecticides remains a big challenge due to its rapid resistance development potential as well as the impact of these chemicals on nontarget organisms. Thus, in search of alternate and novel pest management strategies RNA interference (RNAi) has come up as potential future tool in this direction. The present study targets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 101 publications
0
28
0
Order By: Relevance
“…A slightly different strategy was used in sweet potato whitefly ( Bemisia tabaci ). Researchers mixed dsRNAs specific to endonucleases in the gut with target gene dsRNAs with the result that suppression of the target transcripts and mortality increased by 4‐ to 10‐fold 30 . In addition, Ae.…”
Section: Strategies For Enhancing Rnai Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…A slightly different strategy was used in sweet potato whitefly ( Bemisia tabaci ). Researchers mixed dsRNAs specific to endonucleases in the gut with target gene dsRNAs with the result that suppression of the target transcripts and mortality increased by 4‐ to 10‐fold 30 . In addition, Ae.…”
Section: Strategies For Enhancing Rnai Efficiencymentioning
confidence: 99%
“…Recent studies have provided insights into strategies for enhancing RNAi efficiency in insect pests even further by manipulating the structure of dsRNA molecules, 27 targeting multiple transcripts using a single dsRNA construct, 28 adding repeats of the same dsRNA sequence, 29 mixing dsRNAs, 30 or using other small RNA species (reviewed in Flynt 31 ). Studies have shown that adding additional gene targeting sequences 28 or adding repeats of the same targeting sequence 29 to a dsRNA enhances the toxicity of dsRNAs to two-spotted spider mite (Tetranychus urticae) or P. xylostella, respectively, in feeding assays.…”
Section: Modification Of the Dsrna Sequencementioning
confidence: 99%
See 1 more Smart Citation
“…Still, incremental improvements in the field continue to being made. For example, use of carbon quantum dots conjugated to dsRNA and additional knockdown of gut nucleases that are responsible for degradation of dsRNA have recently been explored (Kaur et al 2020 ). Looking ahead, a COVID-19-fueled explosion of RNA research, especially on the topic of RNA delivery, will undoubtfully have a profound impact on RNA use in the fields outside human medicine (Coccia 2021 ; Cheng et al 2020 ; Miao et al 2019 ; Pardi et al 2018 ).…”
Section: Whiteflies Endosymbionts and Ipm: The Terms Of A Challengementioning
confidence: 99%
“…RNAi-based studies in whiteflies show significant knockdown of a wide set of gene targets, with reviews by Kaur et al (2020) [119], Luo et al (2017) [24] and others (e.g., and references therein: [120][121][122][123][124][125][126][127][128]. The earliest RNAi in whitefly, B. tabaci, used dsRNA's of actin, BtSnap and chickadee [129].…”
Section: Introductionmentioning
confidence: 99%